A comprehensive analysis of aroma compounds and microstructure changes in brown rice during roasting process. (December 2018) - Shi, Yi; Wang, Lingling; Fang, Yong; Wang, Hongpan; Tao, Hongling; Pei, Fei; Li, Peng; Xu, Baocai; Hu, Qiuhui
Abstract: Roasting of brown rice not only forms the aroma compounds but also leads to a complete alteration of the microstructure, but the change mechanism during the roasting process is still unclear. Sensory evaluation, electronic nose, gas chromatography–tandem mass spectrometry and scanning electron microscope were combined to investigate the changes of aroma compounds and microstructure during roasting process. Eleven categories of volatile compounds were detected, and the roasting process made an increase in the content of heterocycle compounds and a decrease in the types and content of hydrocarbons and benzene derivatives. Furans and pyrazines made a great contribution to the aroma quality. Furfural, 5-methyl furfural, 2, 5-dimethylpyrazine, 2-methylpyrazine, 2-ethyl-6-methylpyrazine and 2-ethyl-3, 5-dimethylpyrazine were the main flavor compounds in the roasted brown rice. The microstructure change of brown rice during roasting was found to have a major impact on the volatilization of aroma compounds. Highlights: Brown rice flavor profiles were evaluated using sensory evaluation and E-nose. Aroma compounds of roasted brown rice were identified using HS-SPME-GC-MS/MS. Relationship between the changes in aroma compounds and microstructure was studied. Furans and pyrazines were main aroma components in roasted brown rice.